2020
DOI: 10.17220/mojet.2021.9.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Is phubbing a matter for educators: A case for pre-service and in-service teachers

Abstract: Becoming one of the indispensable tools of our daily life, mobile phones have accelerated the pace of our life by facilitating our business affairs. In addition to the good aspects of these tools reshaping even our habits, they also have various psychological and physiological damages. One of the behaviors for which the cell phone is considered as harmful is phubbing. Phubbing is defined as giving the perception of the individual to his/her mobile phone, not to these people during the communication with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
5
2
0
Order By: Relevance
“…However, although the differences were not significant, it was determined that female participants exhibited more phubbing. This finding was in line with the literature (Guazzini et al, 2019;İlic & Tanyeri, 2021;Parmaksız, 2019). On the other hand, it was concluded that males were more phubbed when compared to females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, although the differences were not significant, it was determined that female participants exhibited more phubbing. This finding was in line with the literature (Guazzini et al, 2019;İlic & Tanyeri, 2021;Parmaksız, 2019). On the other hand, it was concluded that males were more phubbed when compared to females.…”
Section: Discussionsupporting
confidence: 92%
“…Because of the above-mentioned factors and, therefore, the phubbing behavior was expected to increase during the pandemic. On the other hand, the findings were consistent with the literature (Balta et al, 2020;İlic & Tanyeri, 2021). It was suggested that this could be because individuals did not leave their homes regularly, and they may have responded to the related items due to social desirability, even if they were engaged in phubbing behavior.…”
Section: Discussionsupporting
confidence: 88%
“…This result coincides with the result of the study on school psychological counselors conducted by Aydoğdu and Çevik (2020). It also corroborates with the result of study on teachers and teacher candidates conducted by İliç and Tanyeri (2021). However, it is not consistent with studies on university graduates (Roberts et al, 2014) and university graduates (Karadağ et al, 2015).…”
Section: Characteristicsupporting
confidence: 83%
“…In addition, they suggested that phubbing should be investigated amongst the teachers. On the other hand, 46 in-service and 247 pre-service teachers participated in the study in which İliç and Tanyeri (2021) aimed to examine the status of phubbing and being phubbed according to age and gender. It was seen that there was no difference in terms of gender and age, but the phubbing behavior tended to increase as they got older.…”
mentioning
confidence: 99%
“…A seven-point Likert scale questionnaire was used for the study to collect data. Findings revealed that pre-service teachers were more in the case of being both phubbee (x̄Pre-service teacher = 79.65 > x̄In-service teacher = 72.89) and phubber (x̄Pre-service teacher = 43.54 > x̄In-service teacher = 38.39) compared with the in-service teachers [24].…”
Section: Literature Reviewmentioning
confidence: 95%